Morphological prognostic factors determining distant metastasis in infiltrating breast carcinomas - Wen F. Zhang, Juan P. Diaz, Rowan T. Finch (Open Journal of Physicians and Surgeons, 2024)
"The research investigates morphological prognostic factors that play a significant role in determining the likelihood of distant metastasis in infiltrating breast carcinomas. By analyzing various morphological characteristics of tumor tissue, such as histological grade, tumor size, lymphovascular invasion, and lymph node involvement, the study aims to identify key factors that can predict the risk of metastatic spread. Understanding these morphological prognostic indicators is essential for risk stratification, treatment planning, and improving outcomes for patients with breast cancer. The findings from this research may contribute to more personalized and effective management strategies tailored to the prognostic profile of individual breast cancer patients, ultimately enhancing patient care and survival rates.